Just Adapt: Engaging Disadvantaged Young People in Planning for Climate Adaptation - Davies, Anna R. (2021)
The visibility of young people in climate change debates has risen significantly since the inception of the Fridays for Future movement, but little is known about the diversity of positions, perspectives and experiences of young people in Ireland, especially with respect to climate change adaptation planning. To close this knowledge gap, this article first interrogates key emergent spaces of public participation within the arena of climate action in Ireland in order to identify the extent of young people’s participation and whether any specific consideration is given to disadvantaged groups. It then tests the impacts of workshops specifically designed to support disadvantaged young people’s engagement with climate change adaptation which were rolled out with a designated Delivering Equality of Opportunity in Schools school in inner-city Dublin, Ireland. We found limited attention to public participation in climate change adaptation planning generally, with even less consideration given to engaging young people from disadvantaged communities. However, positive impacts with respect to enhanced knowledge of climate change science and policy processes emerged following participation in the workshops, providing the bedrock for a greater sense of self-efficacy around future engagement with climate action amongst the young people involved. We conclude that what is needed to help ensure procedural justice around climate action in Ireland are specific, relevant and interactive educational interventions on the issue of climate change adaptation; interventions which are sensitive to matters of place and difference.